Can overexploited fisheries recover by self-organization? Reallocation of fishing effort as an emergent form of governance. (September 2018) - Brochier, T.; Auger, P.; Thiao, D.; Bah, A.; Ly, S.; Nguyen-Huu, T.; Brehmer, P.
Abstract: Owing to high costs and difficulties in implement control, fisheries are less regulated than terrestrial activities. In areas of weak governance, self-regulation is often the rule. Understanding the underlying bio-economic mechanisms that drive such fishery systems is crucial for decision making on how to support real fishermen communities. Fishing effort reallocation occurs when economic yield drops, suggesting a feedback between fishermen's mobility and local overexploitation. The nature of this feedback is addressed here by using a bio-economic modelling approach applied to a Senegalese fishery. The white grouper is a highly valued commercial fish that has suffered intense exploitation in Senegal and was predicted to collapse due to a lack of fishery regulation combined with high demand. Surprisingly, our analysis of landings and associated price variability suggests that a slow recovery of this fishery is now underway. Motivated by this finding, two models were implemented that account for artisanal fishermen's mobility and variable prices. Both models provided the same insight: fishing effort mobility combined with variable fish prices induced a shift from local overexploitation to sub-regional sustainable exploitation. Considering that fishing effort mobility has steeply increased in recent years, this mechanism might have significantly contributed to the recent observed trends in prices and landings for this fishery. More generally, these bio-economic models suggest that spatial reallocation of fishing effort acts as emergent governance in under regulated areas that allows, in some cases, the recovery of an overexploited species. Highlights: Modelling of feedbacks between fishermen's mobility and local overexploitation. Fishermen's mobility and fish market dynamics can function as a self-regulating system. Probable unexpected recovery of an high value overexploited fish species in Senegal. Self-regulation processes must be taken into account by managers.